Communication from the Governor of Virginia transmitting a series of resolutions adopted by the Ohio Legislature : January 22, 1860 (Document (Virginia. General Assembly. Senate), 1860)
January 21, 1861 Communication to the General Assembly from Governor John Letcher regarding various Ohio anti-slavery resolutions, which the governor found highly objectionable.